(untitled) (Revista de Artes Marciales Asiáticas, 2019)
After a radical conversion of the old Okinawan, anti-samurai martial art toti in the 1920s, a new, in effect Japanese modern combat sport, karate, came into being. The very first karate sports contest already took place in 1930. But, at the end of 1950s, karate started to be exported to the Western world as a traditional martial art of Japanese samurai, even if the samurai had not known karate. That then already omnipresent doctrine has allowed no other perception despite the fact that, globally, the prevalent phenomenon in the field has been karate sports contests in bouts and katas. Exposing the concept of karate as a traditional martial art to be an unhistoric, artificial ideological superstructure, this study is based on more than 50 years of accumulated scepticism of the author that has been confirmed through communication with students of various karate styles and the evaluation of several publications and studies. It is hoped that the findings of this basic study will encourage the sports scientific community to favor further research directed to indisputable and unambiguous explanation of karate.